Oral Presentations Abstracts: STEREOTYPING IN ROBOTIC CARE: AN ETHICAL ANALYSIS OF VULNERABILITIES AMONG OLDER PEOPLE IN DIGITALIZED CARE SETTINGS - ELLERICH-GROPPE, Niklas; WEßEL, Merle; SCHWEDA, Mark (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 In light of demographic aging, the change of familial care arrangements, and the lack of skilled caretakers, robotic systems are increasingly discussed as a possible solution for eldercare. Sociopsychological research indicates that the ensuing human-robot interaction involves the same social categories as human-human interaction, e.g., gender, age and ethnicity. Indeed, these categories and related stereotypical markers are even strategically used in technology development to increase the acceptance and efficiency of robotic systems. Especially in vulnerable groups such as older people, however, such stereotyping strategies can be a reason for new vulnerabilities in digitalized care settings and cause serious moral problems that need critical reflection. In our contribution, we provide a systematic ethical analysis of stereotyping in robotic eldercare. Starting from the conceptual distinction between agency-based and harm-based conceptions of vulnerability, we explore potential moral issues and conflicts in the implementation of stereotypical care robots for older people and detect particularly serious challenges regarding users’ autonomy and wellbeing. Against this backdrop, we propose and discuss possible solutions like the explanation, neutralization or queering of care robots. Thus, we contribute to the theoretical conceptualization of older people’s vulnerabilities in increasingly digitalized care settings and draw conclusions for ethically sensitive technology development in eldercare.